EFFECT OF EXOGENOUS MELATONIN AND CHITOSAN TREATMENTS ON QUALITY AND BIOCHEMICAL CHANGES OF ‘BALADY BANZAHIR’ LIMES DURING SHELF LIFE - A. D. Al-Qurashi; M. A. Awad (Journal of Animal and Plant Sciences, 2023)
Limes undergo metabolic changes during shelf life resulting in rind disorders and green color fading that decrease fruit marketing.To retain fruit quality, some alternatives have been tested in attempts to retain quality and delay senescence during shelf life. In a completely randomized design experiment, the effect of 0.5 mMmelatonin (MT) and 1% chitosan (CT) postharvest dipping either alone or in combination on quality of mature-green ‘Balady Banzahir’ limes during 20 days of shelf life at 23± 1oC and 60–70%RH were evaluated. MT or CT treatments retained fruit quality during shelf life measured as higher green peel color (lower a* values) and titratable acidity (TA) and lower weight loss, total soluble solids (TSS)/TA ratio compared to that of untreated ones. Vitamin C content increased until 8 days in all treatments followed by a dramatic decrease thereafter and was higher in treated fruit than the control. Total flavonoid content (TFC) in peel increased with fluctuation until 16 days but sharply decreased thereafter while, in pulp it decreased with fluctuation in all treatments. In both peel and pulp, treated fruit retained higher TFC content than the control. Antioxidant activity increased with fluctuations in both peel and pulp and was higher in treated fruit than the control. MT or CT treatment showed higher peroxidase (POD) and lower PPO activities during shelf life than the control. However, MT and CT combination treatment provided no further positive effects on most quality parameters. Overall, postharvest dipping in 0.5 mM MT or 1% CT could be an effective treatment to maintain quality of ‘Balady Banzahir’ limes during 16 days of shelf life.
Keywords: Citrus aurantifolia Swingle; Melatonin; Chitosan; Shelf life; Quality